1986
DOI: 10.1002/ajh.2830220412
|View full text |Cite
|
Sign up to set email alerts
|

DDAVP in acquired von Willebrand syndrome associated with multiple myeloma

Abstract: The response to a single intravenous infusion of 1-deamino-8-D-arginine vasopressin (DDAVP, desmopressin) was studied in two patients with acquired von Willebrand syndrome associated with IgG-kappa myeloma. Following infusion of DDAVP (0.3-0.4 micrograms/kg), prolonged bleeding time was normalized; plasma ristocetin cofactor activity, von Willebrand factor antigen, and factor VIII activity were remarkably increased; and high-molecular-weight forms of von Willebrand factor were demonstrated by crossed immunoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…More recently, it has been shown that vWf fragmentation occurs due to in-vivo proteolysis in the patients with CMPD (Budde et al 1986;Lopez-Fernandez et al 1987), and that abnormal vWf structure was not corrected even if blood was obtained in the presence of protease inhibitors (Lopez-Fernandez et al 1987). It is important to determine whether or not these vWf abnormalities are present in each patient with CMPD, because when bleeding episodes occur, the administration of cryoprecipitate or desmopressin (DDAVP) may be effective, as demonstrated in several patients with acquired vWf abnormalities (Budde et al 1984;Mannucci et al 1984;Takahashi et al 1986b).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that vWf fragmentation occurs due to in-vivo proteolysis in the patients with CMPD (Budde et al 1986;Lopez-Fernandez et al 1987), and that abnormal vWf structure was not corrected even if blood was obtained in the presence of protease inhibitors (Lopez-Fernandez et al 1987). It is important to determine whether or not these vWf abnormalities are present in each patient with CMPD, because when bleeding episodes occur, the administration of cryoprecipitate or desmopressin (DDAVP) may be effective, as demonstrated in several patients with acquired vWf abnormalities (Budde et al 1984;Mannucci et al 1984;Takahashi et al 1986b).…”
Section: Discussionmentioning
confidence: 99%
“…10 The antibiotic ristocetin promotes binding of the vWF to the platelet receptor glycoprotein Ib.11 Low levels of vWF, abnormal vWF-multimer composition, and defects in the vWF-binding sites all result in an impaired ristocetin-induced platelet aggregation,12-14 which in some cases can be normalized by DDAVP. 15 It has been suggested that DDAVP might be used to reduce the blood loss after cardiac surgery.6"17 To confirm this, a double-blind placebo-controlled clinical trial of DDAVP on postoperative bleeding in 100 patients was initiated. To investigate the mechanisms behind such a possible effect, it was of interest to study not only the levels of vWF: Ag and VIII: C but also platelet function in relation to the treatment.…”
mentioning
confidence: 99%
“…The additional mechanisms, although appearing to be implausible, remain to be investigated as follows: (1) the Ig preparation used may have anti-idiotypic antibodies or a direct effect on antibodyproducing cells [1][2][3][4], or (2) the Ig preparation may have an activity in stimulating endothelial cells, thus producing and releasing more VWF [1][2][3][4]. In contrast, for AVWS of the nonantibody type, another mechanism, such as the selective absorption of VWFMs on clonal lymphocytes or plasma cells [22][23][24], has been postulated, because some clonal cells in those patients may express platelet glycoprotein Ib, a VWF receptor, on their surface. However, this is not the case in our patient.…”
Section: Discussionmentioning
confidence: 99%